PROBLEMATIKA GPAI DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP IT MIFTAHUL KHAIR KECAMATAN NARMADA KABUPATEN LOMBOK BARAT: Problematika Guru Pendidikan Agama Islam - Hukmi, Hidayatun (Universitas Yudharta Pasuruan, 2024)
This article discusses several problems of PAI teachers during the learning process in the classroom, such as problems found in students, namely lack of interest in learning, lack of concentration in student learning, various student characters and the teacher's lack of ability in technology in implementing the learning curriculum, and what solutions teachers should implement in addressing this problem. This observation aims to find out the problems or complaints of teachers who teach, especially PAI teachers, in the era of implementing the Merdeka curriculum, whether the achievement of learning objectives has met the target or not. So it is important for teachers to have good creativity and it is also important for a teacher to know the character and background of students to make it easier to take an approach that suits the integrity of the student. Therefore, the author raised this problem into an article using a qualitative approach that describes the information available in the field.